USIA KEHAMILAN IBU MEMPENGARUHI KELUARAN BAYI DENGAN BERAT BADAN LAHIR RENDAH - Ria Pancawardani; Rizky Amelia; Sri Wahyuni (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
Low birth weight (LBW) infants are one of the risk factors that contribute to infant mortality, especially during the perinatal period. The incidence of LBW babies occurs every year at the Puledagel Health Center, namely in 2018 there were 13 cases (6.07%), in 2019 there were 12 cases (5.4%), and in 2020 to September there were 15 cases (8 ,7%).The purpose of this research is to find out the factors that influence the incidence of LBW and to find out whether there is a relationship between the independent variable and the dependent variable. The dependent variable of this study was low birth weight (LBW) infants, while the independent variables of this study were maternal age, education, parity, gestational age, gestational age, preeclampsia, ANC quantity, LILA, and Hb levels. The research design used analytic observation with a case control approach with a sample population of 132 respondents who were taken by total sampling technique for LBW and random sampling technique for LBW.The results of the study indicate that the independent variable that affects the incidence of low birth weight babies (LBW) is the mother's gestational age. Maternal gestational age produces a p-value of 0.001 , so that this variable has a significant relationship with the incidence of low birth weight (LBW) infants. Variables that do not affect the incidence of LBW are age, education, parity, pregnancy interval, preeclampsia, quantity of ANC, LILA, and Hb levels.